2013
DOI: 10.3174/ajnr.a3733
|View full text |Cite
|
Sign up to set email alerts
|

DWI Reversal Is Associated with Small Infarct Volume in Patients with TIA and Minor Stroke

Abstract: BACKGROUND AND PURPOSE:More than half of patients with TIA/minor stroke have ischemic lesions on early DWI, which represent irreversibly damaged tissue. The presence and volume of DWI lesions predict early deterioration in this population. We aimed to study the rate and implications of DWI reversal in patients with TIA/minor stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
1
23
0
2
Order By: Relevance
“…Reversal of diffusion restriction, although uncommon, has been previously reported in acute stroke, especially in those with smaller baseline lesions. 6,7 In this patient, the imaging biomarkers for TIA/stroke fluctuated on par with the clinical changes ( figure 1). This case demonstrates that a clinical improvement can be associated with resolution of the DWI abnormality and that depending on the timing of the baseline scan, the acute MRI may be negative in the setting of fluctuating neurologic abnormalities.…”
Section: Practical Implicationsmentioning
confidence: 85%
“…Reversal of diffusion restriction, although uncommon, has been previously reported in acute stroke, especially in those with smaller baseline lesions. 6,7 In this patient, the imaging biomarkers for TIA/stroke fluctuated on par with the clinical changes ( figure 1). This case demonstrates that a clinical improvement can be associated with resolution of the DWI abnormality and that depending on the timing of the baseline scan, the acute MRI may be negative in the setting of fluctuating neurologic abnormalities.…”
Section: Practical Implicationsmentioning
confidence: 85%
“…DWI reversal is uncommon in large strokes 19 but is much more frequent for the small DWI lesions encountered in TIA and minor stroke. 20 When these lesions do persist, they frequently lead to a nonspecific, small, hyperintense signal in a subcortical area without evidence of cavitation. On a blind reading of a 90-day scan, which is equivalent to ordering a scan in a delayed …”
Section: Discussionmentioning
confidence: 99%
“…In our study, final infarct volumes were virtually not smaller than the baseline DWI, supporting that sustained DWI lesion reversal is infrequent in patients accept reperfusion therapy within 6 h after stroke onset. A recent study just demonstrated that DWI reversal is rarely seen but more likely to occur in those with smaller baseline lesions, which should not significantly affect the accuracy of penumbra definition .…”
Section: Discussionmentioning
confidence: 99%